2013
DOI: 10.1177/1359105312471567
|View full text |Cite
|
Sign up to set email alerts
|

Clown intervention to reduce preoperative anxiety in children and parents: A randomized controlled trial

Abstract: This study investigated whether a clown doctor intervention could reduce preoperative anxiety in children hospitalized for minor surgery and in their parents. A randomized controlled trial was conducted with 77 children and 119 parents: the clown group consisted of 52 children accompanied in the preoperating room by their parents (n = 89) and two clowns while the comparison group consisted of children accompanied by the parents only. The clown intervention significantly reduced the children's preoperative anxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
113
0
9

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(130 citation statements)
references
References 33 publications
8
113
0
9
Order By: Relevance
“…The presence of a clown has been found to reduce the child’s anxiety (Dionigi, Sangiorgi, & Flangini, 2014; Felluga et al, 2016; Goldberg et al, 2014; Kocherov et al, 2016; Meiri, Ankri, Hamad-Saied, Konopnicki, & Pillar, 2016; Messina et al, 2014; Vagnoli, Caprilli, & Messeri, 2010; Vagnoli, Caprilli, Robiglio, & Messeri, 2005; Weintraub et al, 2014) and feelings of boredom, loneliness and sadness (Finlay, Baverstock, & Lenton, 2014; Mansson, Elfving, Petersson, Wahl, & Tunell, 2013; Meiri et al, 2016). Also, a few studies showed that a clown intervention is able to reduce anxiety in parents (Agostini et al, 2014; Fernandes & Arriaga, 2010; Wolyniez et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of a clown has been found to reduce the child’s anxiety (Dionigi, Sangiorgi, & Flangini, 2014; Felluga et al, 2016; Goldberg et al, 2014; Kocherov et al, 2016; Meiri, Ankri, Hamad-Saied, Konopnicki, & Pillar, 2016; Messina et al, 2014; Vagnoli, Caprilli, & Messeri, 2010; Vagnoli, Caprilli, Robiglio, & Messeri, 2005; Weintraub et al, 2014) and feelings of boredom, loneliness and sadness (Finlay, Baverstock, & Lenton, 2014; Mansson, Elfving, Petersson, Wahl, & Tunell, 2013; Meiri et al, 2016). Also, a few studies showed that a clown intervention is able to reduce anxiety in parents (Agostini et al, 2014; Fernandes & Arriaga, 2010; Wolyniez et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is considered that as much the illness as the internment configure stress generating situations, fear and anxiety, context on which the clowns interventions are based 4,6,[9][10][11][12][13] .Therefore, we propose a short discussion on the physiology of stress for understanding the effect of obtaining better responses to the patients' and companions treatments, the ones who were in contact with the clowns 4,6,14,15 .…”
Section: Physiologic Contextmentioning
confidence: 99%
“…Common signs of these reactions to stress are alterations of the pulse, breathing frequency and skin temperature, that in some studies are used as parameters for evaluation of emotional well-being 4,6,14 . Like this, interventions that aim to reduce the stress levels provoked by the illness and by the internment, for clinical treatment, surgical procedure, anaesthetic 13 or sedative 16 , can contribute to avoid the onset of complications and associated pathologies, promoting even the patients response to the treatment 10,12 .…”
Section: Physiologic Contextmentioning
confidence: 99%
See 2 more Smart Citations